Oil extraction from spent coffee ground (SCG) using manual extraction method employing hexane as a solvent / Azimah Salihfudin - Salihfudin, Azimah (2023)
Coffee consumption has a long history among Malaysians and was deeply rooted in their culture. Urbanization and busy lives were two factors influencing Malaysia's rise in coffee consumption. The quantity of wasted coffee grounds (SCG) in our nation has increased as a result of all the coffee that has been made. SCG, a renewable resource, was frequently employed in the various coffee industries. Untreated SCG, however, has detrimental agronomic and environmental effects because of their high noxious chemical content (phenols, caffeine, and tannins). Therefore, the goal of my study was to use hexane to extract oil from SCG in order to provide the best yield possible at various periods. Hexane was a useful solvent for my research, which focused on how the extraction time for each 10 g of dried spent coffee powder changed. Obtaining the optimum yield in the allotted period was the major motivation. The project was completed as per our anticipated recommendation. According to our tastes, the 10 g of (SCG) extract has to be used within 40 minutes to get the optimal yield. The outcome demonstrated that time affects how quickly oil was extracted. Hexane was used as a solvent, which resulted in a higher yield of the finished product, which is 11.6550%. It was thought that understanding and using (SCG) would be able to stop and decrease environmental problems.